BUSINESS RECOVERY STRATEGY AND STRENGTHENING THE COMPETITIVE ADVANTAGE OF THE MEETING POINT CAFE AFTER THE OPERATIONAL CRISIS DUE TO THE COLLAPSE OF THE ROOF OF THE ANWA MERUYA PADEL COURT IN INDONESIA - Elang Muhammad Dewa Rizqi; Bagus Dwi Prasetiyo; Kerinda Swary Br Tarigan; Muhammad Royyan Arrosyid; Tiara Puspa (International Journal of Small and Medium Enterprises and Business Sustainability, 2025)
The cafe industry in Indonesia is growing rapidly as part of the experience-based food and beverage sector centered on lifestyle and social interaction. These characteristics, while advantageous, simultaneously render the industry highly vulnerable to external disruptions, particularly regarding safety issues and business environment reputation. This study aims to comprehensively analyze the business recovery strategy and competitive advantage strengthening of Titik Temu Café following an operational crisis triggered by the collapse of a padel court roof in the Anwa Meruya area. Negative perceptions regarding environmental safety significantly impacted visitor numbers and daily revenue (declining by over 50%), despite the incident occurring outside the cafe premises. This research employs a mixed-method approach driven by a qualitative case study design, supported by quantitative strategic tools (QSPM). Data collection involved semi-structured interviews with internal parties, direct observation, and analysis of internal documents and media reports. Strategic management tools facilitated the analysis, including PESTEL, Porter’s Five Forces, VRIO, SWOT–TOWS, and the Quantitative Strategic Planning Matrix (QSPM). Results indicate that external environmental turbulence and increased consumer risk perception primarily influenced the business performance decline. The QSPM analysis further identifies Digital Recovery as the priority strategy. This study recommends crisis communication strategies and operational adjustments as short-term recovery steps, alongside utilizing customer experience-based digitalization as a long-term strategy to strengthen competitive advantage.